Paradigma Pembelajaran Sejarah Dengan Pendekatan Interdisipliner Dan Multidimensional - Andre Mustofa Meihan Andre (LPPM Press, 2026)
This study aims to examine the paradigm of history education through an interdisciplinary and multidimensional approach based on the ideas of Sartono Kartodirdjo. The research employs a qualitative literature review method, drawing upon the works of Sartono Kartodirdjo and relevant journal articles published between 2021 and 2026. Data analysis was conducted using content analysis and hermeneutic interpretation to deeply analyze key concepts. The findings indicate that Sartono Kartodirdjo’s ideas offer a robust theoretical contribution to transforming history education from a conventional model to one that is more integrative, critical, and contextual, specifically through the application of interdisciplinary and multidimensional approaches. The interdisciplinary approach enables the integration of various disciplines to achieve a comprehensive understanding of historical events, while the multidimensional approach offers a broader perspective by considering social, economic, political, and cultural aspects. However, implementation faces challenges such as limited teacher competence and a scarcity of learning resources. Consequently, strategic efforts are required regarding curriculum development, teacher capacity building, and the provision of innovative learning resources. This study contributes conceptually to the development of a history education paradigm that is more relevant to the demands of 21st-century education.